Shank3 Transgenic and Prenatal Zinc-Deficient Autism Mouse Models Show Convergent and Individual Alterations of Brain Structures in MRI - Schoen, Michael; Asoglu, Harun; Bauer, Helen F.; Müller, Hans-Peter; Abaei, Alireza; Sauer, Ann Katrin; Zhang, Rong; Song, Tian-jia; Bockmann, Juergen; Kassubek, Jan; Rasche, Volker; Grabrucker, Andreas M.; et al. (Frontiers in Neural Circuits, 2019)
Research efforts over the past decades have unraveled both genetic and environmental factors, which contribute to the development of autism spectrum disorders (ASD). It is, to date, largely unknown how different underlying causes result in a common phenotype. However, the individual course of development and the different comorbidities might reflect the heterogeneous genetic and non-genetic contributions. Therefore, it is reasonable to identify commonalities and differences in models of these disorders at the different hierarchical levels of brain function, including genetics/environment, cellular/synaptic functions, brain regions, connectivity, and behavior. To that end, we investigated Shank3 transgenic mouse lines and compared them with a prenatal zinc-deficient (PZD) mouse model of ASD at the level of brain structural alterations in an 11,7 T small animal magnetic resonance imaging (MRI). Animals were measured at 4 and 9 weeks of age. We identified a decreased total brain volume (TBV) and hippocampal size of Shank3−/− mice but a convergent increase of basal ganglia (striatum and globus pallidus) in most mouse lines. Moreover, Shank3 transgenic mice had smaller thalami, whereas PZD mice had this region enlarged. Intriguingly, Shank3 heterozygous knockout mice mostly showed minor abnormalities to full knockouts, which might reflect the importance of proper Shank3 dosage in neuronal cells. Most reported volume changes seemed to be more pronounced at younger age. Our results indicate both convergent and divergent brain region abnormalities in genetic and non-genetic models of ASD. These alterations of brain structures might be mirrored in the reported behavior of both models, which have not been assessed in this study.